2005
DOI: 10.1021/jp050957u
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of a Synthetic Clay with Tetrahedral Charges:  A Multidisciplinary Experimental and Numerical Study

Abstract: The interaction of water with a synthetic saponite clay sample, with a layer charge of 1 per unit cell (0.165 C m(-2)), was investigated by following along water adsorption and desorption in the relative pressure range from 10(-6) to 0.99 (i) the adsorbed amount by gravimetric and near-infrared techniques, (ii) the basal distance and arrangement of water molecules in the interlayer by X-ray and neutron diffraction under controlled water pressure, and (iii) the molecular structure and interaction of adsorbed wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
126
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(144 citation statements)
references
References 82 publications
18
126
0
Order By: Relevance
“…That on layer abundance was considered to vary linearly from (2% when the relative proportion of a given layer is 100% or 0% to (5% when this layer represents 50% of the total layers. corresponds to ∼5 and ∼3H 2 O molecules per cation for the low-and high-charge saponite, respectively, in agreement with results obtained by Rinnert et al 40 on similar samples. These values are also consistent with the three-dimensional (3D) structure determination obtained for Ca-, Sr-, Li-, Ba-, or Nasaturated vermiculite minerals in which the cation hydration shell was found to not exceed 4 H 2 O molecules per cation with a coordination similar to a flat tetrahedron.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…That on layer abundance was considered to vary linearly from (2% when the relative proportion of a given layer is 100% or 0% to (5% when this layer represents 50% of the total layers. corresponds to ∼5 and ∼3H 2 O molecules per cation for the low-and high-charge saponite, respectively, in agreement with results obtained by Rinnert et al 40 on similar samples. These values are also consistent with the three-dimensional (3D) structure determination obtained for Ca-, Sr-, Li-, Ba-, or Nasaturated vermiculite minerals in which the cation hydration shell was found to not exceed 4 H 2 O molecules per cation with a coordination similar to a flat tetrahedron.…”
Section: Discussionsupporting
confidence: 92%
“…The investigated saponites were prepared at ISTO (Orléans, France) by hydrothermal treatment as described in detail elsewhere, 40 before being sodium saturated. 20 Their structural formulas are the following: Na x (Si 8-x ,Al x )(Mg 6 )O 20 (OH) 4 , with x ) 0.8 and 1.4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The swelling properties of clays have been studied extensively, both experimentally (Weiss et al, 1990;Cases et al, 1992;Bérend et al, 1995;Michot et al, 2002;Rinnert et al, 2005;Trausch et al, 2006;Salles et al, 2008) and theoretically (Boek et al, 1995a,b;de Siqueira et al, 1997;Young and Smith, 2000;Hensen et al, 2001;Hensen and Smit, 2002;Whitley and Smith, 2004;Tambach et al, 2004;Liu and Lu, 2006;Smith et al, 2006;Tambach et al, 2006) and are now relatively well understood. Mooney et al 3 (1952a,b) were among the first authors to show that smectites are able to sorb up to half their mass in water and that the water sorption behavior is strongly dependent on the nature of the exchangeable cation.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between the particle and the vicinal water becomes more significant as the temperature decreases and the viscosity increases (Wolfe et al, 2002). Recent studies have shown the presence of ordered 10 water near interfaces in biological (Cooke and Kuntz, 1974;Snyder et al, 2014), metallic (Michot et al, 2002) and clay (Yu et al, 2001;Rinnert et al, 2005) particles, a notion that is also supported by molecular dynamics simulations (Lupi et al, 2014;Cox et al, 2015). In a groundbreaking work, Anderson (1967) found strong evidence of ice formation several molecular diameters away from the clay-water interface.…”
Section: Introductionmentioning
confidence: 89%